Reviewing the Implication of RCEP in the Development of Indonesian Investment Law - Febriyanti, Diyah Anggun (Law Research Review Quarterly, 2024)
One of the biggest challenges facing both foreign and domestic investors in Indonesia has always been the issue of investment regulation. After the RCEP Agreement was ratified, this study was carried out to examine the issue of investment regulation in Indonesia, with a focus on Law No. 11 of 2020 on job creation. It also examined the significance of the RCEP, particularly with regard to the advancement of investment law in Indonesia. In this normative study, the legal materials were analyzed using a descriptive-qualitative method. On the basis of legal standards, the data was processed methodically. There are shortcomings in the regulation of investments, including a lack of transparency, community involvement, investment protection, the execution of fair and equal treatment, and legal certainty, even though Law No. 11 of 2020 has an impact on numerous legislative amendments. The ratification of the RCEP will provide Indonesia with prospects to expand market access, provided that the response to the agreement is positive. As a result, the Indonesian government must lift certain restrictions, facilitate economic transactions, adapt laws and regulations as needed, and uphold the public interest.